Single‐Step Solid‐State Scalable Transformation of Ni‐Based Substrates to High‐Oxidation State Nickel Sulfide Nanoplate Arrays as Exceptional Bifunctional Electrocatalyst for Overall Water Splitting. Issue 6 (1st May 2022) - Bahuguna, Gaurav; Cohen, Adam; Harpak, Nimrod; Filanovsky, Boris; Patolsky, Fernando
Abstract: Hydrogen, undoubtedly the next‐generation fuel for supplying the world's energy demands, needs economically scalable bifunctional electrocatalysts for its sustainable production. Non‐noble transition metal‐based electrocatalysts are considered an economic solution for water splitting applications. A single‐step solid‐state approach for the economically scalable transformation of Ni‐based substrates into single‐crystalline nickel sulfide nanoplate arrays is developed. X‐ray diffraction and transmission electron microscopy measurements reveal the influence of the transformation temperature on the crystal growth direction, which in turn can manipulate the chemical state at the catalyst surface. Ni‐based sulfide formed at 450 °C exhibits an enhanced concentration of electrocatalytically‐active Ni 3+ at their surface and a reduced electron density around sulfur atoms, optimal for efficient H2 production. The Ni‐based sulfide electrocatalysts display exceptional electrocatalytic performance for both oxygen and hydrogen evolution, with overpotentials of 170 and 90 mV respectively. Remarkably, the two‐electrode cell for overall electrolysis of alkaline water demonstrates an ultra‐low cell potential of 1.46 V at 10 mA cm −2 and 1.69 V at 100 mA cm −2 . In addition to the exceptionally low water‐splitting cell voltage, this self‐standing electrocatalyst is of binderfree nature, with the electrode preparation being a low‐cost and single‐step process, easily scalable to industrial scales. Abstract : A universal approach for the scalable transformation of Ni‐substrates to novel Ni 3+ ‐enriched NiS nanoplates is developed. The NiS‐based electrocatalyst synergizes the enhanced chemical, structural, and morphological properties in a single material, leading to an exceptional electrocatalytic performance with a cell voltage of 1.46 V for overall water splitting.